Pengaruh Penambahan Dinding Geser Terhadap Perilaku Struktur pada Gedung Bertingkat 10 Lantai di Kota Malang - Bara, R.; Priskasari, E.; Manaha, Y.P. (Tadulako University, 2025)
Building planning with earthquake-resistant structures is carried out to reduce the risk of loss and loss of life during earthquakes, especially in areas with high earthquake risk. This planning aims to evaluate the effect of adding shear walls on the structural behavior of a 10-story building in Malang City. Shear walls are generally used to increase structural stiffness and strengthen the structural system in resisting earthquake forces. With the addition of shear walls, better control of inter-story deviations where the value is significantly reduced compared to being designed as a single system. Shear walls or moment-resisting frames must be able to withstand at least 25% of the design earthquake force. Structural analysis is carried out with the ETABS 19 civil engineering assistance program using building technical data, material data, and building design drawings. The analysis includes determining dimensions based on SNI 2847: 2019 and loading and structural control based on SNI 1726: 2019. The results of the structural analysis show that with the addition of shear walls, the structural elements used are more effective and do not reduce the structure's ability to withstand earthquake loads or gravity loads. The planned shear wall has been able to accept more than 50% of the existing earthquake force, this result has met the minimum requirements for the load carried by the shear wall. The resulting drift also does not exceed the permissible drift, although there is a fairly large difference in the drift value. However, the determination of the location of the shear wall must still be adjusted to the needs and adjust the design of the planned building